Advance Directives in the Neurocritically Ill: A Systematic Review. Issue 8 (August 2020) - Sutter, Raoul; Meyer-Zehnder, Barbara; Baumann, Sira M.; Marsch, Stephan; Pargger, Hans
Abstract : Objectives: To determine the frequency of advance directives or directives disclosed by healthcare agents and their influence on decisions to withdraw/withhold life-sustaining care in neurocritically ill adults. Data Sources: PubMed, Embase, and Cochrane databases. Study Selection: Screening was performed using predefined search terms to identify studies describing directives of neurocritically ill patients from 2000 to 2019. The review was registered prior to the screening process (International Prospective Register of Systematic Reviews identification number 149185). Data Extraction: Data were collected using standardized forms. Primary outcomes were the frequency of directives and associated withholding/withdrawal of life-sustaining care. Data Synthesis: Out of 721 articles, 25 studies were included representing 35, 717 patients. The number of studies and cohort sizes increased over time. A median of 39% (interquartile range, 14–72%) of patients had directives and/or healthcare agents. The presence of directives was described in patients with stroke, status epilepticus, neurodegenerative disorders, neurotrauma, and neoplasms, with stroke patients representing the largest subgroup. Directives were more frequent among patients with neurodegenerative disorders compared with patients with other illnesses ( p = 0.043). In reference to directives, care was adapted in 71% of European, 50% of Asian, and 42% of American studies, and was withheld or withdrawn more frequently over time with a median of 58% (interquartile range, 39–89%). Physicians withheld resuscitation in reference to directives in a median of 24% (interquartile range, 22–70%). Conclusions: Studies regarding the use and translation of directives in neurocritically ill patients are increasing. In reference to directives, care was adapted in up to 71%, withheld or withdrawn in 58%, and resuscitation was withheld in every fourth patient, but the quality of evidence regarding their effects on critical care remains weak and the risk of bias high. The limited number of patients having directives is worrisome and studies aiming to increase the use and translation of directives are scarce. Efforts need to be made to increase the perception, use, and translation of directives of the neurocritically ill. Abstract : Supplemental Digital Content is available in the text.